P-709 Fine-tuning IVF laboratory key performance indicators of the Vienna consensus according to female age. (30th June 2022) - Zaca', C; Coticchio, G; Vigiliano, V; Lagalla, C; Nadalini, M; Tarozzi, N; Borini, A
Abstract: Study question: Is the Vienna consensus appropriate to monitor IVF laboratory outcomes of treatments involving women of different age ranges? Summary answer: Most IVF laboratory key performance indicators(KPIs) are reliably applicable irrespective of female age, while total good blastocyst rate should be adjusted according to female age What is known already: The IVF laboratory is central to ART treatments. This demands methodical and precise monitoring of the performance. To assess laboratory efficiency, the Vienna consensus identified a set of relevant performance indicators(PIs) and KPIs applicable to a "reference population" defined by female age <40years, exclusion of PGT cases and use of own fresh oocytes and ejaculated sperm. It is known that women older than 39years – whose treatment outcome is affected by reduced oocyte quality–represent an increasingly large proportion of IVF patients. Thus, in this subgroup of patients the relevance of the Vienna indicators to treatments of remains to be demonstrated. Study design, size, duration: Reported data concern a retrospective, single-center cohort analysis of 862 ART cycles carried out between January 2014 and May 2021. Inclusion criteria were indication for IVF/ICSI, blastocyst culture of all embryos formed in each cohort, use of own ejaculated spermatozoa (fresh or frozen), and complete cycles, i.e. those whose all embryos were transferred, cryopreserved or disposed of. Cancelled and PGT cycles were not included Participants/materials, setting, methods: The overall population was divided into two groups according to female age: Vienna consensus (≤39 years) and older female age(≥40 years). We measured a selection of the Vienna performance indicators and KPIs, with a focus on measures relevant to embryo cleavage and blastocyst formation. Assessment of fertilization, cleavage and blastocyst rates was carried out. To assess more comprehensively blastocyst quality and quantity, we estimated the total usable blastocyst rate(TBUR). Finally, blastocyst cryosurvival rate was assessed. Main results and the role of chance: No differences were observed in fertilization and embryo cleavage KPIs between the Vienna consensus and the older female age groups (standard IVF fertilization, 67.2 vs. 67.3; ICSI fertilization, 72.3 vs. 75.3; Day 2 development, 57.6% vs 58.7%; Day 3 development, 52.4% vs. 50.7 %, respectively). TBUR was lower in the older female age group (45.5% vs. 33.4% p < 0.001). This outcome decreased steadily with increasing female age. Clinical outcome significantly decreased with increasing female age. Implantation rate decreased from 34.3% in the Vienna consensus group to 16.9% in the older female age group (p<.001). Cumulative CPR showed a similar trend decreasing from 52.4% to 23.9% (p<.001). In the two populations, TBUR was further assessed after normalization of the number of retrieved oocytes. Rates were comparable in cycles with only few (1- 5 oocytes) collected oocytes (51.9% and 45.5%, p=ns). In cycles with 6-10, 11-15 and>15 collected oocytes TBUR was lower in older patient groups(p < 0.01). Univariate and multivariate logistic regression analysis showed female age as a factors independently associated with TBUR. Higher female age was associated with a reduced probability to achieve a TBUR greater than 40%. Limitations, reasons for caution: The study design is retrospective and requires further refinement to control for factors that may impact clinical outcome Wider implications of the findings: The study confirms the general validity of the Vienna Consensus but also indicate a need for fine-tuning in relation to factors intrinsic to gamete quality that can impact laboratory outcomes. Trial registration number: Not applicable